Intervention skills : process consultation for small groups and teams - Reddy, W. Brendan (Jossey-Bass Pfeiffer San FranciscoUS, 1994)
Defines group process consultation. Examines topics including: the phases and sub-phases of group consultation; the type and depth of intervention; and, the competencies needed by consultants. Answers a number of questions frequently asked by group process consultants.